The complete practical encyclopedia of fitness training body-shape, stamina, power - Wadsworth, Andy (Lorenz Books, 2009)
The ultimate do-it-yourself guide to exercising for fitness, strength, weight loss and flexibility, with expert training tips and advice on health, safety, essential equipment, goals and motivation.